Rural Urbanization and Urban Transformation in Quanzhou, Fujian - Tan, Chee-Beng; Ding, Yuling (Anthropologica, 2022)
This article examines rural urbanization and urban transformation in Quanzhou city in Fujian. The administrative urbanization of villages and the impact on the residents are examined. The article shows that the scale and speed of China’s urbanization is due to interaction between industrial development, including rural industrialization, and intervention by the state-socialist government. By comparing two localities, Chendai and Shudou, the article examines two distinct kinds of rural urbanization. The first area industrialized and urbanized with out being officially classified as urban; the second area industrialized and only recently became urbanized despite having been previously classified as urban.